What the students expect and perceive about trustworthiness? - Ibrahimi, Mensur; Mohd Ali, Hairuddin (IIUM Press, 2011)
It is a simple study that trying to examine the gap between the students' expectation on trustworthiness and their perceived trustworthiness. The study formulated four research questions. The implications and recommendation for future research were also presented.